Sosialisasi Pengenalan Pajak dan Audit pada Remaja Karang Taruna - Muhammad Agus Kurniawan; Asih Handayani; Febiyanti Febiyanti; Hanifa Rahmi; Sheirly Roseliae (Universitas Pamulang, 2020)
In Indonesia, the increase in accounting activity is so rapid, that it is undeniable that the need for the world of work, especially the demand for tax and audit services to conduct assessments and audits, has also increased. The public accountant profession is a profession that is trusted by the community. The implementation of community service (PKM) which involves youth and the management of RT 006 Penunggangan Utara Village, Pinang District, Tangerang City. The purpose of this Community Service (PKM) is to introduce taxes and audits to the community, especially for youth in Penunggangan Utara Village, Pinang District, Tangerang City. With the implementation of this Community Service (PKM) activity, it is expected to provide benefits to the participants for the material that has been conveyed. Suggestions for community service activities (PKM), namely the need for further socialisation for teenagers.